P-008 Simulated diagnostic cerebral angiography in neurosurgical training: a pilot program. (12th July 2011) - Spiotta, A; Rasmussen, P; Masaryk, T; Benzel, E; Schlenk, R
Abstract : Introduction: Surgical simulation provides a zero-risk setting in which skills can be obtained through repetition. Advanced, technically accurate simulation systems that provide sensory feedback can further aid the trainee in developing and refining the mechanical skills required for the procedure. We studied the feasibility and utility of simulated diagnostic cerebral angiography among neurosurgical residents and fellows using an endovascular biplane angiography simulator. Methods: Ten neurosurgical residents and four neurointerventional fellows were recruited into a standardized training protocol consisting of a didactic, demonstration and hands-on learning environment. The Simbionix simulator (Simbionix USA Corp, Cleveland, Ohio, USA), was employed. Participants were instructed to catheterize (in order) the right internal carotid artery, left internal carotid artery and left vertebral artery. The task was repeated five times by the participants. Total procedure and fluoroscopy times were recorded in minutes and seconds. Volume of contrast administered and complications were also recorded. Violations of safe technique were recorded. Results: All participants demonstrated improvement over the five trials. There were no dissections, however residents performed actions that were perceived as potentially dangerous. Fellows performed the procedure with superior technique. Residents performed the task with an initial total procedure and fluoroscopy time of 6.6±4.3 min and 4.9±3.7 min, respectively and improved on the fifth trial (3.4±1.3 min; p=0.03 and 2.3±0.78 min; p=0.004). Residents approximated the efficiency of fellows for the third and fourth trial. Conclusions: We have demonstrated that incorporating an endovascular simulator is feasible for training purposes in a neurosurgical residency program and provided the first evidence that it could facilitate the transfer of skills obtained in real world angiography.